Enhance radio resource allocation techniques for fractional frequency reuse base station in mobile WiMAX cellular network - Mohammed Khalid Salman, Fadhil (Universiti Malaysia Perlis (UniMAP), 2014)
Doctor of Philosophy in Computer Engineering